Cohesive Devices Function within Toulmin’s Argument Structure: A Discourse Analysis of EFL Students’ Argumentative Essay - Setiyono, Wahyu; Widhiyanto, Widhiyanto (Jurnal Bahasa Inggris, 2026)
This study examines how cohesive devices function within the components of Toulmin’s Model of Argumentation in EFL undergraduate students’ argumentative essays. Despite extensive research on cohesion in academic writing, few studies have explicitly explored the functional relationship between cohesive choices and argumentative structure, particularly in the Indonesian EFL undergraduate context. Employing a qualitative discourse analysis design, the study analyzed five argumentative essays produced by students enrolled in a Factual and Critical Writing course at a public university in Indonesia. Drawing on Halliday and & Hasan’s (1976) cohesion framework and Toulmin’s (1958) argumentation model as complementary analytical lenses, the analysisi identified and classified cohesive devices before mapping their rhetorical functions onto each argument component. The findings reveal three principal patterns. First, conjunction and reference were the most dominant cohesion categories, while substitution and ellipsis were entirely absent. Second, adversative conjunctions most consistently supported the claim and rebuttal components, whereas lexical cohesion – when realized through collocation and synonymy – most effectively reinforced data and warrant construction. Third, the backing component was absent from all five essays, and rebuttal moves were uniformly incomplete across the corpus. These findings demonstrate that cohesive density does not automatically produce argumentative strength, as the rhetorical effectiveness of cohesive devices depends on their functional appropriateness, referential precision, and the propositional richness of the content they connect. The study concludes with pedagogical recommendations for integrating function-focused cohesion instruction with Toulmin-based argumentative scaffolding in EFL writing courses.